Pharmacokinetics of 5-Aminofluorescein-Albumin, a novel fluorescence marker of brain tumors during surgery - Ding, Reinhard; Frei, Eva; Fardanesh, Mahmoudreza; Schrenk, Hans-Hermann; Kremer, Paul; Haefeli, Walter E. (Journal of clinical pharmacology, 2011)
In a phase I/II study, the new fluorescence marker 5-aminofluorescein covalently bound to human serum albumin (AFL-HSA) was intravenously administered to 10 patients with brain tumor 1 to 4 days before surgery, and AFL-HSA kinetics were determined to assess the optimum timing of dye administration. AFL-HSA was determined in serum and brain tissue by size exclusion chromatography with fluorescence detection. AFL-HSA disposition was quite similar to albumin kinetics with small volumes of distribution (volume of central compartment [Vc] = 2.4 L; volume of distribution [Vdβ] = 6.8 L; volume at steady state [Vss] = 5.9 L), a low clearance (mean Cl = 16.85 mL/h), and a long elimination half-life (mean T½β = 307 hours). Predicted peak concentrations in the peripheral compartment occurred at 80.9 hours, the time point of optimal fluorescence intensity observed in brain tumors during surgery.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 13.06.2022